Temporal and spatial population dynamics of the nomadic short‐eared owl across the western United States. Issue 3 (6th February 2023) - Miller, Robert A.; Buchanan, Joseph B.; Pope, Theresa L.; Carlisle, Jay D.; Moulton, Colleen E.; Booms, Travis L.
Abstract: The short‐eared owl ( Asio flammeus ) is a species of conservation concern in the western United States, and populations are declining throughout its range. Because of its low site fidelity, nomadic lifestyle, and irruptive breeding dynamics across large landscapes, estimating trends at regional or broader scales is difficult. To address that challenge, we recruited community‐science participants to implement a multi‐year survey of short‐eared owls across a study area encompassing 8 western states: California, Idaho, Montana, Nevada, Oregon, Utah, Washington, and Wyoming. We stratified our study area by potential habitat, established 50 spatially balanced transects per state, each with 8–11 survey points, and visited each transect twice per year to perform a 5‐minute point count. From 2018–2020, transect occupancy rates of short‐eared owls were highly variable within individual states but reasonably stable over our study area. California, Idaho, Utah, and Washington were the only states where occupancy rates were stable year to year, with the most stability in Utah and Washington. More monitoring may be warranted to address spatial and temporal variability in abundance of this species that may be influenced by small‐mammal cycles. Our results illustrate the large movements of individuals across regions that may be required to support the North American population, emphasizing the need for broad geographic monitoring and conservation strategies for short‐eared owls. Abstract : The short‐eared owl has low site fidelity, a nomadic lifestyle, and irruptive population dynamics across large landscapes making monitoring difficult. Their breeding densities shift across state boundaries in unpredictable ways.